Nlrc3-like is required for microglia maintenance in zebrafish. (20th June 2019) - Wang, Tienan; Yan, Bo; Lou, Liang; Lin, Xi; Yu, Tao; Wu, Shuting; Lu, Qing; Liu, Wei; Huang, Zhibin; Zhang, Mingjie; Zhang, Wenqing; Wen, Zilong
Abstract: Microglia are tissue-resident macrophages residing in the central nervous system (CNS) and play critical roles in removing cellular debris and infectious agents as well as regulating neurogenesis and neuronal activities. Yet, the molecular basis underlying the establishment of microglia pool and the maintenance of their homeostasis in the CNS remain largely undefined. Here we report the identification and characterization of a mutant zebrafish, which harbors a point mutation in the nucleotide-binding oligomerization domain (NOD) like receptor gene nlrc3-like, resulting in the loss of microglia in a temperature sensitive manner. Temperature shift assay reveals that the late onset of nlrc3-like deficiency leads to excessive microglia cell death. Further analysis shows that the excessive microglia death in nlrc3-like deficient mutants is attributed, at least in part, to aberrant activation of canonical inflammasome pathway. Our study indicates that proper regulation of inflammasome cascade is critical for the maintenance of microglia homeostasis.